\(\dfrac{9}{23}\left|2x-3\right|+\left(7y+17\right)^2\ge0\forall x,y\)
Dấu '=' xảy ra khi \(\left(x,y\right)=\left(\dfrac{3}{2};-\dfrac{17}{7}\right)\)
\(\dfrac{9}{23}\left|2x-3\right|+\left(7y+17\right)^2\ge0\forall x,y\)
Dấu '=' xảy ra khi \(\left(x,y\right)=\left(\dfrac{3}{2};-\dfrac{17}{7}\right)\)
\(\left|x-1\right|+\left|2y-4\right|=2\)
\(\left(2x-3\right)^2+\left(y-3\right)^2=0\)
\(\frac{x-241}{17}+\frac{x-220}{19}+\frac{x-195}{21}+\frac{x-166}{23}=10\)
\(ss;\left(-32\right)^9;\left(-18\right)^{13}\)
Tính nhanh
\(c,\dfrac{-5}{13}-\left(\dfrac{3}{5}+\dfrac{3}{13}-\dfrac{4}{10}\right)\)
\(d,\left(\dfrac{1}{9}-\dfrac{9}{17}\right)+\dfrac{3}{6}-\left(\dfrac{12}{17}-\dfrac{1}{2}\right)+\dfrac{5}{9}\)
Bài 1:
a,\(3^7\) : \(3^5\)- \(\left(\dfrac{5}{17}\right)^0\) b,\(\left(\dfrac{5}{2}\right)^{13}\) : \(\left(\dfrac{1}{2}+2\right)^3\) c, 8.\(\left(\dfrac{1}{4}\right)^3\) +\(\left(\dfrac{2}{27}\right)^0\) - \(\dfrac{1}{8}\)
Bài 2 :
a, \(\dfrac{3^4.4^4}{6^4}\) b,\(\dfrac{15^3}{10^3}\) c, \(\dfrac{4^2.12^5}{9^2.2^{10}}\) d, \(\dfrac{6^2+5.2^2+4}{15}\)
Bài 3 :
a, \(\dfrac{\left(\dfrac{2}{3}\right)^3.\left(\dfrac{-3}{4}\right)^2.\left(-1\right)^5}{\left(\dfrac{2}{5}\right)^2.\left(\dfrac{-5}{12}\right)^2}\) b,\(\dfrac{6^6+6^3.3^3+3^6}{-73}\)
Mọi người giúp mình nhé mình sẽ cho bạn 1 like
\(\left[\left(\dfrac{-3}{8}+\dfrac{11}{23}\right):\dfrac{5}{9}+\left(\dfrac{-5}{8}+\dfrac{12}{23}\right):\dfrac{5}{9}\right].\dfrac{11}{235}\)
\(\left(3-x\right)^3=-\dfrac{27}{64};\left(x-5\right)^3=\dfrac{1}{-27};\left(x-\dfrac{1}{2}\right)^3=\dfrac{27}{8};\left(2x-1\right)^2=\dfrac{1}{4};\left(2-3x\right)^2=\dfrac{9}{4};\left(1-\dfrac{2}{3}\right)^2=\dfrac{4}{9}\)
Tìm x:
1) \(\text{(x−1):0,16=−9:(1−x)}\)
2) \(\left(\left|x\right|-\dfrac{3}{2}\right)\left(2x^2-10\right)=0\)
3)\(8\sqrt{x}=x^2\left(x\ge0\right)\)
a)\(\left(\dfrac{5}{9}-\dfrac{\sqrt{9}}{12}\right):\dfrac{3}{4}+\dfrac{11}{3}:\dfrac{3}{4}\) b)\(\left(0,\left(3\right)+\dfrac{\text{|}-2\text{|}}{3}\right):\dfrac{\sqrt{25}}{4}-\left(2^3+3^2\right)^0\)
\(\left(2.\dfrac{2}{15}.\dfrac{9}{17}.\dfrac{3}{32}\right)\div\left(-\dfrac{3}{7}\right)\)
Thu gọn các đơn thức trong biểu thức đại số sau:
C = \(\dfrac{7}{9}x^3y^2.\dfrac{6}{11}axy^3+-5bx^2y^4.-\dfrac{1}{2}axz+ax.\left(x^2y\right)^3\)
D = \(\dfrac{\left(3x4y^3\right)^2.\left(\dfrac{1}{6}x^2y\right)+\left(8x^{n-9}\right).\left(-2x^{9-n}\right)}{15x^3y^2\left(0,4ax^2y^2z^2\right)}\) ( với axyz khác 0)